Trusted Tree-Based Trust Management Scheme for Secure Routing in Wireless Sensor Networks. (10th December 2015) - Hu, Zhi; Bie, Yuxia; Zhao, Hong
The unique characteristics of wireless sensor networks make them susceptible to the attacks. The secure scheme is considered in designing the routing protocol and algorithm. The cryptography and authentication secure technology can defend the external attacks but have no way to protect the network when the internal attacks occur. However, the trust management scheme with attack-resistance and robustness can efficiently detect the internal attack. On the condition of defending the attacks, it is also an issue that the trust management scheme aids routing algorithm to improve the security and performance. In this paper, we proposed a Trusted Tree-based trust management for secure routing in wireless sensor networks. The common attacks are firstly analyzed. And then the dynamic time window is designed in the distributed trust model with the detection of direct trust and indirect trust. Based on the trusted nodes, Trusted Tree is constructed. And the path quality of nodes in Trusted Tree is used as the gradient for routing. Finally, we add Trusted Tree-based trust management into the QoS based routing protocol and algorithm. Experimental results show that the QoS based routing algorithm with Trusted Tree has better performance and security.